Significant enhancement in photocatalytic performance of Ni doped BiFeO3 nanoparticles. (6th June 2018) - Nadeem, M; Khan, Wasi; Khan, Shakeel; Shoeb, Mohd; Husain, Shahid; Mobin, Mohammad
Abstract: In the present work, we have investigated the effect of Ni doping on the microstructure and photocatalytic properties of BiFeO3 samples. All the compositions of BiFe1−x Nix O3 (0 ≤ x ≤ 0.07) have been synthesized via cost effective ethylene glycol based sol-gel method. The Rietveld refinement of the XRD data revealed rhombohedral crystal structure with R3c space group. The FTIR spectroscopy confirms the formation of BiFeO3 compound. UV–visible DRS result affirmed that the band gap of the samples can be tuned towards visible range by the Ni substitution. The photoluminescence spectra indicate lower intensity with the Ni content, signify reduction in recombination rate of the electron-hole pairs. The photocatalytic response of the nanoparticles was examined for the degradation of methylene blue (MB) dye under visible light irradiation and the highest photocatalytic response was observed for 7% Ni doped sample. Therefore, the observed results suggest potential application of the synthesized nanoparticles for wastewater treatment purpose.